IN-DEPTH ANALYSIS OF THE DYNAMICS POST-ISRAEL-PALESTINE CONFLICT 2023: POLITICAL, ECONOMIC, AND SOCIAL IMPLICATIONS FOR THE FUTURE OF ISRAEL - Meyland S. F. Wambrauw; Diego Romario De Fretes; M. Fathun Niam; Arie Fitria; Marzuki, Marzuki (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This in-depth analysis thoroughly examines the intricate dynamics that unfold in the aftermath of the Israel-Palestine Conflict in 2023. The study takes a comprehensive approach, scrutinizing the political, economic, and social dimensions to uncover multifaceted implications that will shape the future of Israel. Politically, the landscape witnesses transformative shifts in governance structures, coupled with significant external influences that will mold the nation's trajectory. Economically, the impact of various sectors' adaptive resilience and sustainable development initiatives on recovery are explored. Socially, the study delves into the challenges posed by inter-community reconciliation, shifts in national identity, and the broader influence of the conflict on social well-being. The findings of this analysis reveal emerging trends and patterns, offering a nuanced understanding of the complex post-conflict dynamics. The implications for future policies and actions are highlighted, emphasizing the imperative for nuanced governance structures that consider historical contexts and prioritize inclusive decision-making processes. Economically, the study underscores the importance of policies prioritizing sustainable development and equitable resource distribution to foster lasting recovery. Socially, addressing challenges related to inter-community understanding and navigating shifts in national identity are identified as pivotal for building a cohesive society post-conflict. In essence, this study contributes valuable insights for policymakers, scholars, and practitioners alike, aiming to inform decisions that will contribute to stability, reconciliation, and sustainable development in the aftermath of the Israel-Palestine Conflict in 2023.